Systematic and comprehensive comparison of two semianalytical models of microbunching instability - S. Di Mitri; G. Campri; F. Elisii; G. Perosa; S. Spampinati (Physical Review Accelerators and Beams)
The systematic comparison of two semianalytical models of microbunching instability affecting electron beams in single pass or recirculating linear accelerators is reported. The comparison is comprehensive of numerous features of the instability, such as low and high gain contributions, either linearized or at second order, coherent synchrotron and edge radiation, and Landau damping by transverse emittance and laser heater, investigated for single and double magnetic bunch length compression. The comparison is enriched by three different expressions—one of which is new—to calculate intrabeam scattering. The inclusion of this effect allows the recovery of agreement with published experimental observations, to date either in disagreement with theory or in partial agreement by virtue of blind fitting of parameters. The study is complemented by the evaluation of beam heating for oblique electron-laser interaction, this scheme being relevant for high repetition rate free-electron lasers, space constrained, or subject to perturbations by the laser heater chicane.